Penerapan Augmented Reality dengan Markerless Pada Aplikasi Pengenalan Jenis Hewan Herbivora, Karnivora, dan Omnivora - Suharni Suharni; Eel Susilowati; Masimbangan S Harlina; Muhammad Hanif (Journal of Information System Research (JOSH), 2023)
An introduction to the types of herbivores, carnivores, and omnivores needs to be given to children aged 4 to 6 years, and elementary school students. Submission of material using books is not enough to stimulate the mind, feelings and attention, hence the children feel bored. Several studies that have implemented still have limitations, such as there are no animation features, sound and screenshot share. The purpose of the application of Augmented Reality (AR) with the markerless method in the application of the introduction of herbivores, carnivores, and omnivores is to be able to display the object in three dimensions accompanied by animation features, sound and share information about the animal to social media. This goal is expected to increase children's desire to know more about various types of animals, and applications made can be fun learning media. The method used in this research is waterfall, and the application software is Unity. Application testing is using the blackbox technique to test the functions of the buttons and features displayed in the application. The results of the application trials show that all the button functions that are tried to be pressed will display the scene as expected and the results are 100% valid. From the results of the application trials, it shows that the application has been successfully created in accordance with the desired goal, which can be used as a learning medium for children.